Policy Implementation the Role of the School Committee in Realizing School Based Management at SMA Negeri 1 Poso - Mohammad Rusli Syuaib (Universitas Muhammadiyah Palu, 2025)
This research aims to find out how the Policy on the Role of School Committees in Realizing School-Based Management in SMA Negeri 1 Poso is implemented. (2) What factors hinder the implementation of the Policy on the Role of School Committees in Realizing School-Based Management in SMA Negeri 1 Poso. The informants in this research were 7 people consisting of 2 school committee administrators and 2 people from School and Community elements, 3 people; Sampling was carried out using a saturated sampling technique. Data was obtained through observation, interviews and distributing questionnaires. Data was analyzed descriptively qualitatively. The research results show that the implementation of the school committee policy on communication indicators is not going well, while the resources and disposition indicators show that the implementation of the policy on the role of the school committee has gone well even though the sub-indicator relating to financial resources is still limited by the school committee. Meanwhile, the factors inhibiting policy implementation that were found were ineffective implementation of socialization, low levels of ability and concern for other stakeholders involving themselves in the management of the school committee.